2011
DOI: 10.4025/actasciagron.v33i3.6734
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activities of bacteria, yeasts and filamentous fungi isolated from coffee fruit (Coffea arabica L.)

Abstract: ABSTRACT. One hundred forty-four microorganisms previously isolated from coffee fruit (Coffea arabica) were grown on casein agar to evaluate their proteolytic activities. Fifty percent of filamentous fungi, 52.5% of bacteria and 2.6% of yeasts were able to secrete proteases. RESUMO. Atividade proteolítica de bactérias, leveduras e fungos filamentosos presentes em grãos de café (Coffea arabica L.). Este trabalho teve por objetivos avaliar a capacidade de secreção de proteases extracelulares por 144 microrganism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…protease determined at 60.34 U/mL in this study was previously reported as 40 mg/mL in the isolate in 2017 (24) to 157.50 U/mg (25). In this study, the Klebsiella aerogenes protease was 33.27 U/mL, previously detected at 14.24 U/mL (26). Similar differences were observed in Stenotrophomonasmaltophilia protease activity which was 57.59 U/mL in this study; nevertheless, it was previously determined at 1.87 U/mg (27) to 418 U/mL (28).…”
Section: Discussionsupporting
confidence: 65%
“…protease determined at 60.34 U/mL in this study was previously reported as 40 mg/mL in the isolate in 2017 (24) to 157.50 U/mg (25). In this study, the Klebsiella aerogenes protease was 33.27 U/mL, previously detected at 14.24 U/mL (26). Similar differences were observed in Stenotrophomonasmaltophilia protease activity which was 57.59 U/mL in this study; nevertheless, it was previously determined at 1.87 U/mg (27) to 418 U/mL (28).…”
Section: Discussionsupporting
confidence: 65%
“…Protease activity was measured as follows: 2.5 mL of yeast culture (~10 8 cells/mL) was added to an Erlenmeyer flask containing 100 mL of YCB medium supplemented with 0.01% sodium caseinate and 0.1% glucose. Flasks were then incubated with agitation (90× g ) at 28°C for 3, 7, and 14 days and growth was determined from the optical density (OD) measurements at 600 nm [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The pure cultures were stored in an ultra-freezer at -80 °C in the same broth culture media used for plating, containing 20% glycerol (w/w). Yeast colonies were characterized for morphology and biochemical assessments as described by [43]. Filamentous fungi were observed with an optical microscope for preliminary identi cation.…”
Section: Methodsmentioning
confidence: 99%